Surgical injury induces local and distant adipose tissue browning. (2nd April 2016) - Longchamp, Alban; Tao, Ming; Bartelt, Alexander; Ding, Kui; Lynch, Lydia; Hine, Christopher; Corpataux, Jean-Marc; Kristal, Bruce S.; Mitchell, James R.; Ozaki, C. Keith
ABSTRACT: The adipose organ, which comprises brown, white and beige adipocytes, possesses remarkable plasticity in response to feeding and cold exposure. The development of beige adipocytes in white adipose tissue (WAT), a process called browning, represents a promising route to treat metabolic disorders. While surgical procedures constantly traumatize adipose tissue, its impact on adipocyte phenotype remains to be established. Herein, we studied the effect of trauma on adipocyte phenotype one day after sham, incision control, or surgical injury to the left inguinal adipose compartment. Caloric restriction was used to control for surgery-associated body temperature changes and weight loss. We characterized the trauma-induced cellular and molecular changes in subcutaneous, visceral, interscapular, and perivascular adipose tissue using histology, immunohistochemistry, gene expression, and flow cytometry analysis. After one day, surgical trauma stimulated adipose tissue browning at the site of injury and, importantly, in the contralateral inguinal depot. Browning was not present after incision only, and was largely independent of surgery-associated body temperature and weight loss. Adipose trauma rapidly recruited monocytes to the injured site and promoted alternatively activated macrophages. Conversely, PDGF receptor-positive beige progenitors were reduced. In this study, we identify adipose trauma as an unexpected driver of selected local and remote adipose tissue browning, holding important implications for the biologic response to surgical injury.